Potential anti-proliferative agents from 1, 4-benzoxazinone-quinazolin-4(3H)-one templates. Issue 24 (15th December 2017) - Bollu, Rajitha; Banu, Saleha; Kasaboina, Suresh; Bantu, Rajashaker; Nagarapu, Lingaiah; Polepalli, Sowjanya; Jain, Nishant
Graphical abstract: A newly synthesized 1, 4-benzoxazinone-acetylphenylallyl quinazolin-4(3 H )-one hybrids7a –n showed moderate to excellent anti-proliferative activity against A549, HeLa, MDA-MB-231human cancer cell lines. Design strategy and anti-proliferative evaluation of new analogues7a –n against A549, HeLa and MD-MB-231. Highlights: Novel 1, 4-benzoxazinone-acetylphenylallyl quinazolins have been synthesized efficiently. Evaluated for their anti-proliferative activity against four human cell lines. Compounds7a –n showed GI50 values ranging from 0.32 to 13.4 µM. 7f, 7j, 7l showed good anti-proliferative activity with GI50 values 0.58, 0.32, 0.37 µM. Abstract: A novel synthetic protocol has been developed for the synthesis of 1, 4-benzoxazinone-acetylphenylallyl quinazolin-4(3 H )-one hybrids7a –n by employing Pd-catalyzed CH arylation in presence of 5–10% phosphine ligand in good to excellent yields and evaluated for their anti-proliferative activity against three cancer cell lines such as A549 (lung), HeLa (cervical), MDA-MB-231 (breast). Compounds7d, 7f, 7l and7n exhibited promising anti-proliferative activity with GI50 values ranging from 0.37 to 2.73 µM respectively against A549, HeLa, and MDA-MB-231, while compound7f showed significant activity against MDA-MB-231 with GI50 value 0.58 µM, 7j showed significant activity against A549 with GI50 value 0.32 µM and7l showed significant activity against HeLa with GI50 value 0.37 µM. This is the first report on the synthesis and in vitro anti-proliferative evaluation of 1, 4-benzoxazinone-acetylphenylallyl quinazolin-4(3 H )-one hybrids.